INTELLECTUAL PROPERTY RIGHTS, INNOVATION AND HEALTHCARE: HARMONIZING THE LEGAL PROVISIONS FOR HEALTHCARE AND PHARMACEUTICAL INDUSTRY - Singh, Dr. Bhupinder (JIPRO: Journal of Intellectual Property, 2023)
The healthcare sector is being impacted by information technology advancements in four key ways: first, a wide range of tasks that were previously performed manually can now be performed by computers; second, some tasks can be outsourced to other countries using affordable communications technology; third, longitudinal and societal healthcare data can now be analysed in acceptable amounts of time; and fourth, the best medical expertise can sometimes be made available. The healthcare industry will increasingly employ a portfolio approach made up of three closely coordinated components that are seamlessly integrated together: healthcare tasks performed by humans on-site; healthcare tasks performed by humans off-site, including tasks performed in other countries; and healthcare tasks performed by computers without direct human involvement. The three-pronged healthcare services paradigm is discussed in this essay along with relevant legal and intellectual property issues.